Calcium alginate / heteropolyacid salt composite material as well as preparation method and application thereof
The preparation of calcium alginate/heteropolyacid salt composite materials by ultrasonic treatment and gas crosslinking solves the problems of high density and low porosity caused by the drying of sodium alginate gel, achieves efficient adsorption of rubidium ions, simplifies the process and reduces costs.
Patent Information
- Application Number
- CN202511064248.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-04
AI Technical Summary
The existing sodium alginate gel drying process results in high internal density, few adsorption sites, and low porosity of the adsorbent, which limits its application range. Furthermore, the existing composite material preparation process is complex or has poor mechanical strength.
By mixing heteropolyacid salts and sodium alginate, introducing gas under ultrasonic action, and crosslinking with a Ca2+-containing solution, a calcium alginate/heteropolyacid salt composite material is formed. Ultrasonic action is used to generate nanoscale and microscale pores and retain the pores during the drying process.
A high-strength, high-porosity composite material was prepared, exposing more adsorption sites and improving the adsorption capacity and ion exchange rate of rubidium ions. The process is simple and low-cost.
Smart Images

Figure CN120885200A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of alginate composite materials, and particularly relates to a calcium alginate / heteropolyacid salt composite material and a preparation method and application thereof. BACKGROUND
[0002] Rubidium (Rb) is a kind of active metal with silver-white metal luster, and is a key element in many high-tech fields due to its unique physical and chemical properties. Rubidium plays an important role in atomic clocks, catalysts, energy conversion, quantum computing and communication, etc. By carrying high-precision rubidium atomic clocks, the Beidou series global satellite navigation system of China has realized sub-centimeter positioning, providing an important guarantee for high-precision navigation and unmanned driving; the incorporation of rubidium can effectively improve the stability and service life of perovskite photovoltaic materials, and is expected to become a key element of the third-generation solar cell industry; 85Rb and 87Rb isotopes are key materials for constructing cold atomic well quantum computing processors and quantum information storage devices, and a thermoelectric transducer made of rubidium, such as used with an atomic reactor, can realize thermal ion thermal nuclear power generation inside the reactor.
[0003] Inorganic ion exchangers have good selectivity and stability, can well resist temperature changes, and are resistant to radiation, and are widely used in the field of separation and extraction. As early as the 1950s, Nature magazine reported that heteropolyacid salts represented by ammonium phosphomolybdate (AMP) have good selectivity adsorption for rubidium and cesium ions, and the desorption of the adsorbed ions from ammonium phosphomolybdate is simple. Ammonium phosphomolybdate has a microcrystalline structure, which greatly limits its practical separation operation, especially column operation. In order to solve the separation difficulty, extensive research has been conducted, and various reagents have been compounded with ammonium phosphomolybdate to improve the performance of ammonium phosphomolybdate. These include coating with organic compounds, loading with silica gel, loading with Al2O3 and zirconium phosphate, etc., which have improved the performance of ammonium phosphomolybdate to varying degrees.
[0004] Alginate has the characteristics of biodegradability and environmental friendliness, and contains rich free hydroxyl and carboxyl functional groups that can rapidly react with divalent metal cations to form gels, making it a good matrix material. Sodium alginate (SA) gels have poor mechanical properties, low stability in application, and are easy to disintegrate and break, and drying will cause high density and fewer adsorption sites inside the adsorbent, greatly limiting its application range. The composite materials obtained by compounding sodium alginate with other materials generally need to be modified to obtain higher porosity, improve the pore structure and expose more adsorption sites to improve the performance of the composite materials. Therefore, how to reduce the volume reduction of the prepared adsorbent during the drying process and reduce the mass transfer resistance to expose more active adsorption sites to increase the adsorption capacity is an urgent problem.
[0005] In the prior art, patent CN101518727A uses calcium alginate-encapsulated ammonium phosphomolybdate to prepare composite adsorbent particles. This method effectively solves the problem of filtration and separation of ammonium phosphomolybdate. However, drying of sodium alginate gel leads to high internal density and fewer adsorption sites of the adsorbent, greatly limiting its application range. Patent CN116532094B uses a mixture of orthosilicic acid solution and sodium alginate, and then mixes it with ammonium phosphomolybdate and crosslinks it with calcium salt. This solves the difficulty of solid-liquid separation of ammonium phosphomolybdate and also introduces orthosilicic acid to improve the mechanical strength. However, drying of sodium alginate-coated ammonium phosphomolybdate composite material leads to high internal density and fewer adsorption sites of the adsorbent, and the problem of low porosity has not been effectively solved. Patent CN116077729B injects a chitosan solution and a sodium alginate solution through a core-shell spinneret to perform gel spinning; the composite is drawn under gravity and enters a mold to form a mixed and uniform sol-gel-like polyelectrolyte composite, which is frozen and dried to obtain a composite sponge with aerogel-like properties. This method obtains a composite material with high porosity. However, this method is complex, as it uses electrostatic spraying and then uses freeze-drying, and the obtained material has poor mechanical strength and high compressibility, and cannot be used in column adsorption. SUMMARY
[0006] The main purpose of the present application is to provide a calcium alginate / heteropolyacid salt composite material, a preparation method thereof and an application thereof, so as to overcome the deficiencies in the prior art.
[0007] To achieve the aforementioned purposes, the technical solutions adopted by the present application include:
[0008] One aspect of the present application provides a preparation method of a calcium alginate / heteropolyacid salt composite material, which includes:
[0009] Mixing the heteropolyacid salt, sodium alginate and water uniformly to obtain a sol;
[0010] Introducing a gas into the sol, and simultaneously performing ultrasonic treatment on the sol, so as to generate nanoscale cavities in the sol by the ultrasonic waves and to generate micrometer-sized bubbles by breaking the introduced gas;
[0011] While the ultrasonic treatment is being performed, the sol is added into a solution containing a Ca2 + soluble salt to perform crosslinking and aging, so as to obtain the calcium alginate / heteropolyacid salt composite material.
[0012] Another aspect of the present application provides a calcium alginate / heteropolyacid salt composite material prepared by the aforementioned preparation method. The calcium alginate / heteropolyacid salt composite material includes uniformly compounded calcium alginate and heteropolyacid salt, and has nanoscale pores and micrometer-sized pores inside.
[0013] Another aspect of the present application also provides a calcium alginate / heteropolyacid salt adsorbent, which includes the aforementioned calcium alginate / heteropolyacid salt composite material.
[0014] Another aspect of the present application also provides the use of the aforementioned calcium alginate / heteropolyacid salt composite material or the aforementioned calcium alginate / heteropolyacid salt adsorbent in adsorbing rubidium ions.
[0015] Compared with the prior art, the technical scheme of the present application has at least the following advantages:
[0016] 1) The preparation method provided by the present application generates cavities of two sizes in the sol-gel through the functions of generating cavities in liquid and ultrasonic breaking of bubbles by ultrasonic waves, and the cavities are successfully retained in the material during the drying process, so the preparation process is simple and the cost is low.
[0017] 2) The calcium alginate / heteropolyacid salt composite material provided by the present application has high strength, high porosity, and many exposed adsorption sites, and has high adsorption capacity and fast ion exchange rate for adsorbing rubidium ions in solution. BRIEF DESCRIPTION OF DRAWINGS
[0018] In order to more clearly illustrate the technical scheme in the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or the prior art description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments described in the present application, and other drawings can also be obtained by those skilled in the art without creative labor on the basis of these drawings.
[0019] Figure 1 The synthesis process diagram of the calcium alginate / ammonium phosphomolybdate composite material in a typical embodiment of the present application;
[0020] Figure 2 The EPMA (20 μm) photo of the calcium alginate / ammonium phosphomolybdate composite material prepared in Example 1 of the present application;
[0021] Figure 3 The EPMA (10 μm) photo of the calcium alginate / ammonium phosphomolybdate composite material prepared in Example 1 of the present application;
[0022] Figure 4 The EPMA (5 μm) photo of the calcium alginate / ammonium phosphomolybdate composite material prepared in Example 1 of the present application;
[0023] Figure 5 The EPMA (2 μm) photo of the calcium alginate / ammonium phosphomolybdate composite material prepared in Example 1 of the present application;
[0024] Figure 6 The element analysis EDS graph of the calcium alginate / ammonium phosphomolybdate composite material prepared in Example 1 of the present application;
[0025] Figure 7Initial Rb concentration for adsorption test + Graph of the effect of initial Rb concentration on the amount of Rb adsorbed by the adsorbent;
[0026] Figure 8 Rb concentration for adsorption test + Langmuir model fit adsorption isotherm on the adsorbent;
[0027] Figure 9 Rb concentration for adsorption test + Freundlich model fit adsorption isotherm on the adsorbent;
[0028] Figure 10 Histogram of equilibrium adsorption capacity of the composite particles prepared for Examples 1-3 and Comparative Examples 1-4 in a 450 mg / L Rb solution of RbCI at 35°C; +
[0029] Figure 11 Histogram of porosity of the composite particles prepared for Examples 1-3 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0030] The present application will be more fully understood by reading the following detailed description in conjunction with the drawings, in which:
[0031] As one aspect of the technical solutions of the present application, a method for preparing a calcium alginate / heteropolyacid salt composite material includes:
[0032] mixing the heteropolyacid salt, sodium alginate, and water uniformly to obtain a sol;
[0033] introducing a gas into the sol while performing ultrasonic treatment on the sol, so that the ultrasonic waves generate nanoscale cavities in the sol and the introduced gas is broken to generate microscale bubbles;
[0034] while the ultrasonic treatment is being performed, adding the sol into a solution containing a soluble salt of Ca2+ + to perform crosslinking and aging, thereby preparing the calcium alginate / heteropolyacid salt composite material.
[0035] In some embodiments, the heteropolyacid salt includes, but is not limited to, any one or a combination of the following two: ammonium phosphomolybdate ((NH4)3[PMo 12 O 36 ]·xH2O) and ammonium phosphotungstate.
[0036] In some embodiments, the gas includes, but is not limited to, air.
[0037] In some embodiments, the Ca 2+ The soluble salt in the soluble salt solution includes, but is not limited to, CaCl2.
[0038] In the present application, for example, when configuring the calcium alginate / heteropolyacid sol, due to the extremely high viscosity of the sodium alginate solution, the functions of generating cavitation in the solution by ultrasonic waves and breaking bubbles by ultrasonic waves can generate two sizes of cavitation in the sodium alginate solution, micrometer level (broken bubbles) and nanometer level cavitation generated by cavitation effect in liquid induced by high-frequency acoustic energy. While generating bubble cavitation, the sol droplets containing cavitation are dropped into the CaCl2 solution, and the Ca 2+ The cross-linking solidification with sodium alginate retains the bubbles and cavitation in the gel, and then drying obtains the porous composite material.
[0039] In some embodiments, the preparation method includes: mixing sodium alginate with water to obtain a sodium alginate solution, and uniformly mixing heteropolyacid salt with the sodium alginate solution to obtain the sol.
[0040] In some preferred embodiments, the mass ratio of the sodium alginate to water is (0.5-1.5):(20-200).
[0041] In some preferred embodiments, the mass ratio of the heteropolyacid salt to the sodium alginate solution is (0.5-5):100.
[0042] In some embodiments, the frequency of the ultrasonic treatment is 20-100 kHz, and the power of the ultrasonic treatment is 20-100 w.
[0043] In some embodiments, the rate of the gas input is 0.5-50 ml / min. Specifically, a gas cylinder, a compressor, etc. can be used to input the gas by a gas pump, but is not limited thereto.
[0044] The preparation method of the present application has a simple process. Compared with the pore-forming methods such as template method, solvent evaporation and phase separation, and chemical additive decomposition method, the present application does not need additional steps, and can realize pore-forming by adding ultrasonic in the raw material mixing process. The preparation method of the present application has low cost, and does not need additional addition of other chemical reagents in the pore-forming process. Although the phase separation method also does not need to add chemical reagents, it needs a freeze-drying process, and the process is complex and the cost is high.
[0045] The present application adopts a pore-forming method of ultrasonic wave plus gas, which can produce pores of different sizes in the material. The cavities produced by ultrasonic wave are generally in the mesopore range, and the cavities of large aperture can be produced by breaking the bubbles with ultrasonic wave.
[0046] In some embodiments, the preparation method comprises: adding the sol into a Ca 2+ -containing soluble salt solution in a dropwise manner to cross-link and age.
[0047] In some embodiments, the Ca 2+ -containing soluble salt solution has a mass fraction of 2%-10%.
[0048] In some embodiments, the preparation method comprises: adding the sol into a Ca 2+ -containing soluble salt solution to cross-link and age, drying, to obtain a calcium alginate / heteropolyacid salt composite material.
[0049] In some preferred embodiments, the aging time is more than 12h.
[0050] In some preferred embodiments, the drying temperature is 30-150℃.
[0051] In some more specific embodiments, as shown in Figure 1 , a preparation method of a calcium alginate / heteropolyacid salt composite material comprises the following steps:
[0052] Step 1): uniformly stirring sodium alginate and water in a ratio of (0.5-1.5):(20-200) to obtain a sodium alginate solution;
[0053] Step 2): uniformly stirring ammonium phosphomolybdate and the sodium alginate solution at room temperature in a ratio of (0.5-5):100 to obtain a uniform sol;
[0054] Step 3): continuously introducing gas into the sol in step 2) by using a gas cylinder, a gas pump (1 in Figure 1 ) and the like, and inserting an ultrasonic wave generator (2 in Figure 1 ) into the sol to continuously produce cavities in the sol by ultrasonic wave and break the introduced gas to produce small bubbles;
[0055] Step 4): continuously dropping the sol into a CaCl2 solution with a mass fraction of 2%-10% by using a peristaltic pump (3 in Figure 1 ), and continuously aging for more than 12h to obtain gel beads;
[0056] Step 5) washing the surface of the obtained gel beads with CaCl2 solution by using secondary water, and detecting the washing liquid with sodium carbonate solution to ensure that the surface of CaCl2 is washed clean;
[0057] Step 6) drying the washed calcium alginate / ammonium phosphomolybdate gel beads at 60℃ to obtain the calcium alginate / ammonium phosphomolybdate composite material.
[0058] Sodium alginate can rapidly react with divalent metal cations to form a gel, has the advantages of rich raw materials, easy availability and low price, and is a good matrix material, but its application is limited by low porosity and less adsorption sites. In the present application, a large number of micro-bubbles exist in the sol by passing in gas, and the method of breaking the bubbles by ultrasonic waves is used to produce cavities in the process of forming the sol-gel adsorbent, and the cavities are retained in the adsorbent during solidification, so that the dried adsorbent has both strong mechanical strength and a large number of micro-pores, overcoming the shortcomings of low porosity and less adsorption sites of existing adsorbents.
[0059] As another aspect of the technical scheme of the present application, it relates to a calcium alginate / heteropoly acid salt composite material prepared by the aforementioned preparation method, which comprises uniformly compounded calcium alginate and heteropoly acid salt, and has nanoscale and microscale pores inside.
[0060] In some embodiments, the porosity of the calcium alginate / heteropoly acid salt composite material is 12-25%.
[0061] In some embodiments, the calcium alginate / heteropoly acid salt composite material is spherical with a diameter of 0.3-1.5mm.
[0062] As another aspect of the technical scheme of the present application, it relates to a calcium alginate / heteropoly acid salt adsorbent comprising the aforementioned calcium alginate / heteropoly acid salt composite material.
[0063] As another aspect of the technical scheme of the present application, it relates to the application of the aforementioned calcium alginate / heteropoly acid salt composite material or the aforementioned calcium alginate / heteropoly acid salt adsorbent in adsorbing rubidium ions.
[0064] The present application will be further described in the following examples, but the present application is not limited in the scope of the examples. The reagents and raw materials used in the following examples are commercially available, and the test methods not specified in the following examples are usually carried out according to conventional conditions or the conditions recommended by the manufacturers.
[0065] Example 1
[0066] The present example provides a preparation method of a calcium alginate / ammonium phosphomolybdate composite material, comprising the following steps:
[0067] Step 1): Put 2g sodium alginate into 100mL water, magnetically stir for 12h to make the system well mixed, to obtain a sodium alginate solution;
[0068] Step 2): Put 4g ammonium phosphomolybdate into the obtained sodium alginate solution, magnetically stir to form a sol;
[0069] Step 3): Insert an ultrasonic generator into the sol, apply ultrasonic waves to the sol while pumping in gas (air) at a rate of 5ml / min using a peristaltic pump, the ultrasonic frequency is 30kHz and the power is 40w;
[0070] Step 4): Use a peristaltic pump to drop the sol (use a 5# needle with a diameter of 0.25mm) into a 4% CaCl2 solution drop by drop to form gel microspheres;
[0071] Step 5): After the dropwise addition is completed, let it stand for 24h;
[0072] Step 6): Use distilled water to remove the residual CaCl2 from the aged gel microspheres;
[0073] Step 7): Dry the gel microspheres at 60°C to obtain dried particles to obtain a calcium alginate / ammonium phosphomolybdate composite material.
[0074] EPMA is used to analyze the surface morphology and element distribution of the dried sample. Figures 2 to 5 The EPMA photo of the dried calcium alginate / ammonium phosphomolybdate composite material of Example 1. As can be seen from the 5μm and 2μm morphologies, a large number of bubble holes are formed by ultrasonic pore-forming during the mixing of the sample, and the bubble holes remain during the volume reduction caused by drying. This will provide ion exchange migration channels for the adsorption process to reduce the mass transfer resistance, and also provide channels for the adsorption sites inside the composite adsorbent, thereby increasing the adsorption capacity. Figure 6 The EDS graph of the element analysis of the calcium alginate / ammonium phosphomolybdate composite material of Example 1. As can be seen from the EDS graph, the Ca element can be uniformly distributed in the dried composite adsorbent, indicating that the sodium alginate and Ca2 + have a good crosslinking reaction. According to the distribution of Mo and P elements, it can be seen that the fine ammonium phosphomolybdate (AMP) crystal particles are uniformly fixed in the calcium alginate matrix, solving the difficulty of filtering AMP powder crystals.
[0075] Example 2
[0076] The present embodiment provides a method for preparing a calcium alginate / ammonium phosphomolybdate composite material, comprising the following steps:
[0077] Step 1): 2g of sodium alginate was put into 200mL of water, and 2g of ammonium phosphomolybdate was added, and the system was stirred magnetically for 12h until it was uniformly mixed to form a sol;
[0078] Step 2): An ultrasonic generator was inserted into the sol, and ultrasonic waves were applied to the sol while a peristaltic pump was used to pump in gas (air) at a rate of 20ml / min, the ultrasonic frequency was 45kHz, and the power was 20w;
[0079] Step 3): The sol solution was dropped into (using a 5# needle with a diameter of 0.25mm) a 10% mass fraction CaCl2 solution drop by drop using a peristaltic pump to form gel microspheres;
[0080] Step 4): After the dropwise addition was completed, the gel microspheres were allowed to stand and age for 24h;
[0081] Step 5): The aged gel microspheres were used to remove residual CaCl2 with distilled water;
[0082] Step 6): The gel microspheres were dried at 60°C to form dry particles to obtain a calcium alginate / ammonium phosphomolybdate composite material.
[0083] Example 3
[0084] The present embodiment provides a method for preparing a calcium alginate / ammonium phosphomolybdate composite material, comprising the following steps:
[0085] Step 1): 2g of sodium alginate was put into 50mL of water, and 2g of ammonium phosphomolybdate was added, and the system was stirred magnetically for 12h until it was uniformly mixed to form a sol;
[0086] Step 2): An ultrasonic generator was inserted into the sol, and ultrasonic waves were applied to the sol while a peristaltic pump was used to pump in gas (air) at a rate of 50ml / min, the ultrasonic frequency was 70kHz, and the power was 50w;
[0087] Step 3): The sol solution was dropped into (using a 5# needle with a diameter of 0.25mm) a 2% mass fraction CaCl2 solution drop by drop using a peristaltic pump to form gel microspheres;
[0088] Step 4): After the dropwise addition was completed, the gel microspheres were allowed to stand and age for 24h;
[0089] Step 5): The aged gel microspheres were used to remove residual CaCl2 with distilled water;
[0090] Step 6): The gel microspheres were dried at 60°C to form dry particles to obtain a calcium alginate / ammonium phosphomolybdate composite material
[0091] Comparative Example 1
[0092] The difference from Example 1 is that no air is passed and no ultrasonic treatment is performed.
[0093] Comparative Example 2
[0094] The difference from Example 1 is that the frequency of the ultrasonic wave is 150 HZ and the power is 100 W during the ultrasonic treatment.
[0095] Comparative Example 3
[0096] The difference from Example 1 is that 10 g of sodium alginate is added to 100 mL of water in step 1) and the sol is dropped into a 20% CaCl2 solution in step 3).
[0097] Comparative Example 4
[0098] The difference from Example 1 is that the rate of gas passing through the peristaltic pump is 100 ml / min.
[0099] Adsorption performance test
[0100] A certain amount of RbCl is accurately weighed and a 450 mg / L adsorbate solution is prepared. 10 mL of the RbCl solution is transferred to a centrifuge tube containing 0.5 g of the adsorbent (wet) and 15 mL of water, and the tube is sealed and placed in a constant-temperature water bath shaker at 35°C for 48 h of equilibrium shaking. The supernatant is removed and diluted, and the equilibrium concentration of each sample is measured by ICP-OES. e The equilibrium adsorption capacity q e is calculated.
[0101] The adsorption capacity is calculated according to the following formula:
[0102]
[0103] In the formula, C0 is the initial concentration of the ion, in mg / L; C e is the equilibrium liquid-phase concentration of the ion, in mg / L; V is the volume of the adsorbate solution, in L; and m AMP is the mass of ammonium phosphomolybdate in the composite adsorbent, in g.
[0104] Porosity test
[0105] After drying, the composite adsorbent prepared in Examples 1-3 and Comparative Examples 1-4 is tested by automatic porosimetry using the mercury intrusion method, with a mercury pressure of 9.2 kPa and an equilibrium time of 10 s.
[0106] See Figure 10 and Figure 11 , Figure 10 and Figure 11The composite material particles prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to a concentration of 450 mg / L Rb at 35°C. + The bar chart shows the equilibrium adsorption capacity and porosity in RbCl solution. It can be seen that Examples 1-3 all yielded high adsorption capacity and porosity.
[0107] Comparing the test results of Example 1 and Comparative Example 1, it can be seen that the porosity of the adsorbent prepared without ultrasonic treatment is only 7.73%, which is 9.20% lower than that of the ultrasonically treated composite material; the equilibrium adsorption capacity is 23.79 mg / g, a decrease of 31.99%. In the composite material without ultrasonic treatment, ammonium phosphomolybdate is coated in the composite material, which reduces the adsorption capacity of the adsorbent and increases the adsorption equilibrium time.
[0108] Comparing the results of Example 1 and Comparative Example 2, it can be seen that the ultrasonic frequency exceeds the range of the present invention, and the equilibrium adsorption capacity is only 10.49 mg / g, representing a decrease of 76.33%. This is because high-frequency and high-power ultrasound can generate high temperatures. Under the action of high-frequency ultrasound and high temperature, ammonium phosphomolybdate decomposes, greatly reducing the adsorption active sites and decreasing the adsorption capacity of the adsorbent.
[0109] Comparing the results of Example 1 and Comparative Example 3, it can be seen that the concentration of sodium alginate solution and the crosslinking agent Ca2 are different. + When the concentration is too high, the porosity of the resulting composite adsorbent is 7.79%, a decrease of 54.04%; the equilibrium adsorption capacity is 25.71 mg / g, a decrease of 42.12%, indicating that the resulting adsorbent is too dense.
[0110] Comparing the results of Example 1 and Comparative Example 4, it can be seen that when the gas flow rate is too fast, the granulation effect of the composite adsorbent is poor. Although the porosity is 25.36%, it cannot have a good loading capacity for ammonium phosphomolybdate and is easy to detach. The adsorption capacity is only 5.36 mg / g.
[0111] The composite material prepared in Example 1 under different conditions Rb + The adsorption experiments, isotherms, and kinetics were analyzed, and the test results are shown in [reference]. Figures 7 to 9 .
[0112] from Figure 7 It can be seen that the adsorption capacity per unit volume gradually increases with the increase of the initial rubidium concentration in the adsorbent. This is mainly because the composite adsorbent is not saturated with adsorption. As the initial rubidium concentration increases, the concentration difference between the adsorbent surface and rubidium increases, and the adsorption driving force increases accordingly. Therefore, the adsorption capacity of the composite adsorbent for rubidium increases with increasing concentration. However, as the rubidium concentration increases, the increasing trend of the equilibrium adsorption capacity gradually slows down, mainly because the adsorption sites on the surface of the composite adsorbent gradually become saturated.
[0113] The equilibrium adsorption data were correlated by Langmuir and Freundlich adsorption isotherm models, and the maximum adsorption capacity q max and Langmuir isotherm adsorption constant K L ; the Freundlich isotherm adsorption constant K F and empirical constant n can be calculated according to the calculation data of Freundlich isotherm equation. The experimental data were fitted according to Langmuir and Freundlich adsorption isotherm equations, as shown in Figure 8 and Figure 9 .
[0114] The Langmuir and Freundlich models have high correlation coefficients at different temperatures, indicating that both models can describe the adsorption behavior of Rb + on the adsorbent material, and it is shown that there are monolayer adsorption and multilayer adsorption in the adsorption process of Rb + on the adsorbent material, which also indicates that the ultrasonic addition in the preparation process of the adsorbent material can increase the probability of adsorbing Rb + . According to the fitting results of Langmuir adsorption isotherm model, the maximum adsorption capacity of the adsorbent material for Rb + is 46.45 mg·g -1 . The fitting results show that the correlation coefficient value of Langmuir model is greater than that of Freundlich model, indicating that the adsorption of Rb + on the surface of the adsorbent material is uniform adsorption, and the parameter 1 / n<1 indicates that there is a chemical adsorption process, which will be beneficial to adsorption.
[0115] In summary, the present application uses ultrasonic waves as a low-cost pore-forming method to disperse pore-forming in alginate composite materials, successfully preparing a calcium alginate gel adsorbent (calcium alginate / ammonium phosphomolybdate composite material), which significantly improves the porosity of the adsorbent by ultrasonic pore-forming technology, exposes more adsorption sites, and thus improves the adsorption capacity and rate of rubidium ions.
[0116] In addition, the present inventors have also carried out tests with other raw materials, process operations and process conditions described in the present specification with reference to the foregoing examples, and all obtained relatively ideal results.
[0117] The above embodiments only express several implementation manners of the present application, and the description is more specific and detailed, but it should not be understood as a limitation on the scope of the patent. It should be noted that for ordinary skilled persons in the art, without departing from the concept of the present application, several modifications and improvements can be made, which are within the scope of protection of the present application. Therefore, the protection scope of the patent of the present application should be subject to the appended claims.
Claims
1. A method for preparing a calcium alginate / heteropolyacid composite material, characterized in that, include: Mix heteropolyacid salts, sodium alginate, and water evenly to obtain a sol; Gas is introduced into the sol, and the sol is simultaneously subjected to ultrasonic treatment, so that the ultrasonic waves generate nanoscale cavities in the sol and break up the introduced gas to generate micron-scale bubbles. During ultrasonic treatment, a sol containing Ca is added. 2+ The calcium alginate / heteropolyacid salt composite material was obtained by cross-linking and aging in a soluble salt solution.
2. The preparation method according to claim 1, characterized in that, The heteropolyacid salt includes any one or a combination of two of ammonium phosphomolybdate and ammonium phosphotungstate; and / or, the gas includes air; and / or, the Ca-containing... 2+ The soluble salts in the soluble salt solution include CaCl2.
3. The preparation method according to claim 1, characterized in that, include: Sodium alginate is mixed with water to obtain a sodium alginate solution, and heteropoly acid salts are mixed evenly with the sodium alginate solution to obtain the sol. Preferably, the mass ratio of sodium alginate to water is (0.5-1.5):(20-200); Preferably, the mass ratio of the heteropolyacid salt to the sodium alginate solution is (0.5-5):
100.
4. The preparation method according to claim 1, characterized in that, The frequency of the ultrasonic treatment is 20-100kHz, and the power of the ultrasonic treatment is 20-100W.
5. The preparation method according to claim 1, characterized in that, The gas is introduced at a rate of 0.5-50 ml / min; Preferably, the gas is introduced via a gas cylinder or a compressor.
6. The preparation method according to claim 1, characterized in that, include: The sol was added dropwise to a Ca-containing container. 2+ Cross-linking and aging are carried out in soluble salt solutions; Preferably, the Ca-containing 2+ The mass fraction of the soluble salt solution is 2%-10%.
7. The preparation method according to claim 1, characterized in that, include: The sol was added to a Ca2+-containing solution. + The calcium alginate / heteropolyacid salt composite material was obtained by cross-linking and aging in a soluble salt solution and then drying. Preferably, the aging time is 12 hours or more; Preferably, the drying temperature is 30-150°C.
8. A calcium alginate / heteropolyacid salt composite material prepared by any one of claims 1-7, comprising uniformly composited calcium alginate and heteropolyacid salt, and having nanoscale pores and microscale pores inside; Preferably, the porosity of the calcium alginate / heteropolyacid composite material is 12-25%; Preferably, the calcium alginate / heteropolyacid composite material is spherical with a diameter of 0.3-1.5 mm.
9. A calcium alginate / heteropolyacid salt adsorbent, characterized in that, Includes the calcium alginate / heteropolyacid salt composite material as described in claim 8.
10. The application of the calcium alginate / heteropolyacid salt composite material of claim 8 or the calcium alginate / heteropolyacid salt adsorbent of claim 9 in the adsorption of rubidium ions.
Citation Information
Patent Citations
Calcium alginate embedded ammonium phosphomolybdate composite adsorbent, and preparation and use of same
CN101518727A
Chitosan / sodium alginate composite sponge and preparation method and application thereof
CN116077729B
Ammonium phosphomolybdate resin particles, their preparation method and application
CN116532094B